الطاقة الشمسية كأداة للحد من التلوث وتعزيز التنمية المستدامة ــ دراسة جغرافية بيئية - فرج, فرج عبد الرحيم (مجلة الاصالة, 2025)
الطاقة الشمسية كأداة للحد من التلوث وتعزيز التنمية المستدامة ــ دراسة جغرافية بيئية